The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/coatings8120451
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low-Temperature Tempering on Microstructure and Properties of the Laser-Cladded AISI 420 Martensitic Stainless Steel Coating

Abstract: Post-treatment is crucial to improve the comprehensive performance of laser-cladded martensitic stainless steel coatings. In this work, a low-temperature tempering treatment (210 °C), for the first time, was performed on the laser-cladded AISI 420 martensitic stainless steel coating. The microstructure and properties of the pre- and post-tempering specimens were carefully investigated by XRD, SEM, TEM, a micro-hardness tester, a universal material testing machine and an electrochemical workstation. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Therefore, the increasing portion of F accounts for the reduction in the microhardness and strength, but the enhancement in the toughness of the specimens with higher V addition, consistent with the previous study [28]. Table 2 lists the data of the Rm, Re, and elongation of the laser-cladded MSS coatings with and without V addition developed in this study, and is compared with other Fe-based MSS coatings prepared by the laser cladding technique from the literature [8,21,25,[29][30][31]. It can be apparently concluded that the 0.5%V-bearing MSS coating achieved in this work exhibits a striking combination of high strength and high ductility.…”
Section: Mechanical Propertiessupporting
confidence: 83%
See 1 more Smart Citation
“…Therefore, the increasing portion of F accounts for the reduction in the microhardness and strength, but the enhancement in the toughness of the specimens with higher V addition, consistent with the previous study [28]. Table 2 lists the data of the Rm, Re, and elongation of the laser-cladded MSS coatings with and without V addition developed in this study, and is compared with other Fe-based MSS coatings prepared by the laser cladding technique from the literature [8,21,25,[29][30][31]. It can be apparently concluded that the 0.5%V-bearing MSS coating achieved in this work exhibits a striking combination of high strength and high ductility.…”
Section: Mechanical Propertiessupporting
confidence: 83%
“…The reasons accounting for the microhardness and tensile strength change of the specimens could be associated with the following factors: On the one hand, the formation of the refined martensite, nano-sized precipitates VN and Cr 23 C 6 can generate fine-grain strengthening and second-phase strengthening effects, which significantly enhances the microhardness and tensile strength [3,8,25]. On the other hand, the ferrite stabilizer element V can promote the F phase formation [17].…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…They showed that high-quality coatings with high hardness (over 60 HRC) and wear resistance can be produced. Zhu et al demonstrated the beneficial effect of Low-Temperature Tempering on the microstructure and properties of martensitic stainless steel coatings produced by laser cladding [32]. They proved that the post-treatment leads to martensite decomposition into finer tempered martensite with precipitations of numerous nano-sized Fe 3 C carbides [32].…”
mentioning
confidence: 99%
“…Zhu et al demonstrated the beneficial effect of Low-Temperature Tempering on the microstructure and properties of martensitic stainless steel coatings produced by laser cladding [32]. They proved that the post-treatment leads to martensite decomposition into finer tempered martensite with precipitations of numerous nano-sized Fe 3 C carbides [32]. Chen et al investigated the laser cladding of Fe-based coatings on rotating shafts made of 35CrMo steel, working in the seawater environment [33].…”
mentioning
confidence: 99%
“…Plasma surfacing is one of the widely used methods for steel surface strengthening [1][2][3] owing to several advantages, including the wide variety of surfacing materials, low dilution rate, and high production efficiency [4,5]. Compared with thermal spraying and chemical deposition, plasma surfacing increases the bonding force of the surfacing layer formed with the matrix, resulting in metallurgical bonding and a thickness larger than that obtained using other methods [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%